Pengaruh Metode Pembelajaran Mind Mapping Terhadap Motivasi dan Hasil Belajar Siswa Pada Mata Pelajaran Dasar-Dasar Teknik Komputer Jaringan dan Telekomunikasi - Mas’ud, Huzaima; Suhada, Sitti; Izah, Nurul; Bouty, Abd. Azis; Pakaya, Nikmasari; Rijal, Bait Syaiful (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2024)
This research is motivated by the lack of motivation and learning outcomes of students in the subject of basic computer network and telecommunication engineering. One of the factors that affect student motivation and learning outcomes is the lack of use of learning methods. The mind mapping learning method is a creative, effective and literally note-taking technique that will map thoughts very simply, so that it can improve student motivation and learning outcomes. This study aims to determine the effect of the mind mapping learning method on student motivation and learning outcomes in the subject of basic computer network and telecommunication engineering of class X TKJ-A with 26 students and class X TKJ-B with 27 students. The instruments used were questionnaires for student learning motivation and test questions (posttest) for learning outcomes. Based on the results of the study based on data analysis and hypothesis testing, a significant value of 0.000 <0.05 was obtained where Ho was rejected and Ha was accepted where the mind mapping learning method had a significant effect on student motivation and learning outcomes. So it can be concluded that the mind mapping learning method has an effect on the motivation and learning outcomes of class X TKJ students in the subject of basic computer network and telecommunications engineering at SMK Negeri 1 Suwawa.Keywords: Mind Mapping learning method, Learning motivation, Learning outcomes